The immunological role of cell wall components from diverse Mycobacterium tuberculosis clinical isolates in regulating HIV-1 replication in human macrophages - Ndengane, Mthawelanga (Division of Medical Microbiology, 2023)
Human immunodeficiency virus type 1 (HIV-1) and Mycobacterium tuberculosis (Mtb) coinfection remains a major global health threat. Both pathogens synergistically drive pathogenesis of the other. The risk of developing active tuberculosis (TB) is increased in people living with HIV-1, even in those receiving antiretroviral therapy (ART), whilst TB was responsible for 15 % of HIV-related deaths in 2020. Mtb co-infection increases the likelihood of transcriptionally activating HIV-1 replication potentially due to bioactive Mtb lipids engaging macrophage surface receptors, thus triggering signaling pathways which activate human transcriptional factors (hTF) and production of inflammatory cytokines capable of activating HIV-1 transcription. This work investigated the hypothesis that clinical Mtb strains with single nucleotide polymorphisms (SNP) in lipid-metabolizing genes, required for cell wall lipid biosynthesis, differentially affect HIV-1 replication and human macrophage inflammatory response during Mtb-HIV-1 co-infection in vitro. Monocyte derived macrophages (MDM) were the predominant model used to investigate this phenomenon. Infections, in the presence or absence of HIV-1 co-infection, were performed using either lineage 2 or lineage 4 clinical strains with non-synonymous SNP in polyketide synthase 2 (pks2) required for sulfolipid 1 (SL-1) biosynthesis and compared to control infections using phylogenetically close clinical strains without the SNP of interest and canonical lineage 2 and 4 laboratory strains (H37RvP1939/T605, CDC1551WT and HN878WT). Secreted cytokines and chemokines were measured in supernatant (SN) by Luminex. The effect of Mtb on HIV-1 viral production was assessed by measuring HIV-1 Gag p24 in the SN of co-infected MDM or SN of HIV-1 infected MDM incubated with conditioned media from Mtb-infected MDM. The influence of Mtb on HIV-1 transcriptional activity was measured using a transgenic cell line (TZM-bl) with Luciferase reporter under HIV-1 long terminal repeat (LTR) expression. The impact of incubating TZM-bl cells in Mtb-induced conditioned media before or after HIV-1 infection was assessed. One pair of phylogenetically close clinical strains with and without a pks2 SNP of interest (EX30Q1939/A605 and MRC16P1939/A605) with interesting lipid and inflammatory phenotypes, and H37RvP1939/T605 as a lineage 4 control, were subject to single nucleotide mutagenesis using recombineering to either revert SNP of interest to match the alleles of H37Rv or introduce the SNP of interest into the control strains. The wild-type and mutant strains were used in a trans-well assay to infect MDM in the presence of HIV-1 co-infection in the top chamber, while simultaneously mimicking the bystander effect of cytokine-mediated HIV-1 regulation in the bottom chamber which was only infected with HIV-1. Results demonstrate there was increased cytokine production by MDM infected with MRC16P1939/A605 in both the presence and absence of HIV-1 co-infection compared to its phylogenetically close paired strain EX30 Q1939/A605. The data shows that there was no difference in LTR activity in TZM-bl cells co-incubated with inflammatory environment between the strains of interests, however co-incubation of TZM-bl cells with Mtb-induced inflammatory environment generally increased LTR activity during HIV-1; a proxy for HIV-1 replication. In the trans-well co-infection assay, a significant positive association between production of HIVp24 and secretion of CCL2 was observed, whilst IL-1β secretion showed a significant negative relationship with the production of HIVp24, with donor variability in baseline cytokine production also associated with the extent of HIVp24, CCL2, IL-1β and IL-8 production. Introduction of the pks2 T605A SNP into H37RvP1939/T605 and reversion in EX30Q1939/A605T significantly modified their inflammatory phenotype. Together these results support the hypothesis that Mtb clinical stains with genetic variation in cell wall lipid biosynthesis impacts the inflammatory milieu and, subsequently, HIV-1 replication during co-infection. The outcome of Mtb-HIV co-infection is therefore not homogenous but contingent on the phenotype of infecting Mtb strain and individual.